1996
DOI: 10.1021/jm950600m
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance and Molecular Modeling Study on Mycophenolic Acid:  Implications for Binding to Inosine Monophosphate Dehydrogenase

Abstract: The conformation of the sodium salt of mycophenolic acid (MPA), a potent inhibitor of inosine monophosphate dehydrogenase (IMPD), derived from 1D DIFNOE and 2D ROESY experiments in water and molecular dynamics (MD) is described. The hexenoic acid side chain conformation consistent with the NMR data was similar to that seen in the X-ray structure of MPA. The solution conformation was applied in a molecular modeling study in order to explore the potential features of enzyme binding. Our results, based on strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The other known compounds isolated from P. kongii including pebrolide (Mccorkindale et al 1981) ( 2 ), 1-deoxypebrolide (Mccorkindale et al 1981) ( 3 ), asperphenamate (McCorkindale et al 1978) ( 4 ), N-benzoyl-phenylalaninol (McCorkindale et al 1978) ( 8 ), orsellinic acid (Fang et al 2012) ( 9 ), mycophenolic acid (Makara et al 1996) ( 10 ), and 5, 7-dihydroxy-4-methylphthalide (Fujimoto et al 1999) ( 11 ), and the other known compounds isolated from P. brasilianum including 12, 13-dihydroxyfumitremorgin C (Inokoshi et al 2013) ( 12 ), verruculogen (Afiyatullov et al 2004) ( 13 ), viridicatumtoxin (Inokoshi et al 2013) ( 14 ), dehydroaustin (Hayashi et al 1994) ( 15 ), austinolide (Lo et al 2012) ( 16 ), neoaustin (Hayashi et al 1994) ( 17 ), brasiliamide A (Fujita et al 2002) ( 18 ), brasiliamide C (Fujita & Hayashi 2004) ( 19 ), and aspterric acid (Shimada et al 2002) ( 20 ), were determined by comparison of those reported spectroscopic data. Among these, aspterric acid is reported from P. brasilianum for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The other known compounds isolated from P. kongii including pebrolide (Mccorkindale et al 1981) ( 2 ), 1-deoxypebrolide (Mccorkindale et al 1981) ( 3 ), asperphenamate (McCorkindale et al 1978) ( 4 ), N-benzoyl-phenylalaninol (McCorkindale et al 1978) ( 8 ), orsellinic acid (Fang et al 2012) ( 9 ), mycophenolic acid (Makara et al 1996) ( 10 ), and 5, 7-dihydroxy-4-methylphthalide (Fujimoto et al 1999) ( 11 ), and the other known compounds isolated from P. brasilianum including 12, 13-dihydroxyfumitremorgin C (Inokoshi et al 2013) ( 12 ), verruculogen (Afiyatullov et al 2004) ( 13 ), viridicatumtoxin (Inokoshi et al 2013) ( 14 ), dehydroaustin (Hayashi et al 1994) ( 15 ), austinolide (Lo et al 2012) ( 16 ), neoaustin (Hayashi et al 1994) ( 17 ), brasiliamide A (Fujita et al 2002) ( 18 ), brasiliamide C (Fujita & Hayashi 2004) ( 19 ), and aspterric acid (Shimada et al 2002) ( 20 ), were determined by comparison of those reported spectroscopic data. Among these, aspterric acid is reported from P. brasilianum for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The hexanoic side chain has a restricted conformation due to the presence of the C7 hydroxy and C5 methoxy groups on the aromatic ring and the E geometry of the side-chain double bond. NMR analysis of apo-MPA in solution suggested that the most likely stable solution configuration involves a bent conformation with the carboxyl group bent toward the aromatic ring rather than being in an extended conformation (although C4‘ to the end of the chain is the most conformationally flexible region) …”
Section: Resultsmentioning
confidence: 99%
“…The protons of the C5 methoxy group (5Me) are not too perturbed suggesting this group is not close to the metal ion despite the apparent closeness to C1‘ and C2‘. Makara et al show that the methoxy group is forced out of the plane of the aromatic ring as a result of interactions with the neighboring methyl and hexanoic acid groups . In apo-MPA the NMR derived distance between the C5 methoxy group and the C1‘ and C2‘ protons is 4.0 Å and 3.3 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This orientation is stabilized by an intramolecular electrostatic interaction between the ribose oxygen and the partially positively charged S/Se atoms (23,24). Modeling studies on MPA, another potent IMPDH inhibitor that binds to the nicotinamide portion of the dinucleotide binding site (63), suggested that MPA binds by adopting an anti-like conformation (64). Thus it appears that the nicotinamide conformation of IMPDH-bound NADH is related to the unusually high affinity of IMPDH for nicotinamide-substituted analogues such as TAD and SAD which lack the positive charge of the NAD + nicotinamide ring and thus are best described as NADH analogues rather than NAD + analogues (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%